Extensor Tenosynovitis due to Mycobacterium marseillense Infection in a Renal Transplant Recipient - Hirase, Takashi (J Am Acad Orthop Surg Glob Res Rev, 2021)
Renal transplant recipients are at an increased risk of atypical nontuberculous mycobacterial (NTM) infections. Infections caused by NTM are uncommon in the general population, rarely occurring in immunocompetent individuals. NTM infections are an uncommon cause of tenosynovitis. Mycobacterium marseillense is a rare, atypical mycobacteria that has been reported to cause pulmonary and cutaneous infections; however, no previous reports of this pathogen causing tenosynovitis exist. This case reports a 73-year-old male renal transplant recipient who presented with chronic extensor tenosynovitis of the right hand caused by M marseillense. The patient was treated with radical extensor tenosynovectomy and 6 months of antibiotic treatment. A review of literature on tenosynovitis caused by atypical mycobacteria was performed. The patient successfully responded to treatment with no complications or recurrence of infection at the 18-month follow-up. Tenosynovitis of the hand caused by atypical mycobacteria is rare. A high index of suspicion is required to prevent a delay in diagnosis, particularly in immunocompromised individuals.